Production of CaO from Golden Snail Shells: Structural and Surface Area Characterization by XRD, FTIR, and BET Analysis - Jeanne Dewi Damayanti; Maria Assumpta Nogo Ole; M. Ilham Nurdin; Arifah Sukasri; Nur Amin Riyadi (Jurnal Kartika Kimia, 2026)
Golden snails are widely recognized as significant pests in Indonesian rice fields because they damage young rice plants by attacking their stems and leaves. Despite their harmful agricultural impact, golden snail shells contain a high calcium carbonate (CaCO₃) content of approximately 60.56%, making them a valuable raw material for calcium oxide (CaO) production through calcination. In this study, golden snail shells were calcined at 700, 800, and 900°C for 5 hours. The resulting CaO materials were characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), and Brunauer Emmett Teller (BET) surface area analysis. The findings demonstrate that calcination temperature significantly influences the physicochemical properties of the produced CaO, particularly its surface area. Among the tested conditions, the sample calcined at 900°C exhibited the highest specific surface area of 244.5211 m²/g, indicating enhanced porosity and a greater number of potential active sites at elevated calcination temperatures.